Removal of phenol and COD via catalytic treatment using activated carbon and alumina with ozone - Saidina Amin, Nor Aishah; Man Singh, Harjit Kaur; Mohd. Yusoff, Mohd. Rashid (SIRIM Berhad, 2005)
The removal of aqueous phenol and COD (chemical oxygen demand) was examined by ozonation, adsorption and catalytic ozonation with granular activated carbon (GAC) and alumina. Adsorption and catalytic ozonation tests were performed on 100 ppm phenol at 30 degree C. Results of the experiments indicated that GAC removed up to 71.2% of phenol and 75.4% of COD in two hours via adsorption, and its potentially a promising adsorbent to remove phenol compared to alumina, which does not remove phenol and COD to any significant extent. Addition of ozone into the system resulted in larger phenol removal with 100% and 95.1% removal achieved by GAC and alumina respectively. However, the COD removal achieved by ozonation with GAC was more complete with 93.4% removal compared to alumina with 57.9% removal. Therefore, combination of ozone with GAC is potentially a suitable alternative to treat wastewater containing phenol.